Haploinsufficiency of BMP4 and OTX2 in the Foetus with an abnormal facial profile detected in the first trimester of pregnancy - Capkova, Pavlina; Santava, Alena; Markova, Ivana; Stefekova, Andrea; Srovnal, Josef; Staffova, Katerina; Durdová, Veronika (Molecular cytogenetics, 2017)
BACKGROUND: Interstitial microdeletion 14q22q23 is a rare chromosomal syndrome associated with variable defects: microphthalmia/anophthalmia, pituitary anomalies, polydactyly/syndactyly of hands and feet, micrognathia/retrognathia. The reports of the microdeletion 14q22q23 detected in the prenatal stages are limited and the range of clinical features reveals a quite high variability. CASE PRESENTATION: We report a detection of the microdeletion 14q22.1q23.1 spanning 7,7 Mb and involving the genes BMP4 and OTX2 in the foetus by multiplex ligation-dependent probe amplification (MLPA) and verified by microarray subsequently. The pregnancy was referred to the genetic counselling for abnormal facial profile observed in the first trimester ultrasound scan and micrognathia (suspicion of Pierre Robin sequence), hypoplasia nasal bone and polydactyly in the second trimester ultrasound scan. The pregnancy was terminated on request of the parents. CONCLUSION: An abnormal facial profile detected on prenatal scan can provide a clue to the presence of rare chromosomal abnormalities in the first trimester of pregnancy despite the normal result of the first trimester screening test. The patients should be provided with genetic counselling. Usage of quick and sensitive methods (MLPA, microarray) is preferable for discovering a causal aberration because some of the CNVs cannot be detected with conventional karyotyping in these cases. To the best of our knowledge, this is the earliest detection of this microdeletion (occurred de novo), the first case detected by MLPA and confirmed by microarray. Literature review of the genotype-phenotype correlation in similar reports leads us to the conclusion that dosage imbalance of the chromosomal segment 14q22q23 (especially haploinsuffiency of the genes BMP4 and OTX2) contributes significantly to orofacial abnormalities. Association of the region with the Pierre Robin sequence appears to be plausible.
Keywords: Micrognathia; First trimester ultrasound; Microdeletion 14q22q23; Pierre Robin sequence